Monitoring Vegetation as Habitat (Paradisaea minor jobiensis Rothschild, 1879) in the Period 2024, 2018, and 2024 to Support Birdwatching Ecotourism in Barawai Yapen Islands Regency Papua - Edoward Krisson Raunsay; Basa T. Rumahorbo; Apriani Herni Rophi; David R. Jesajas; Rudolf Abrauw (Jurnal Penelitian Pendidikan IPA, 2024)
Imbowiari Forest in Barawai Village, Yapen, Papua, has complex flora and fauna biodiversity, including as a habitat for Paradisaea minor jobiensis. In Papua, especially the Yapen Islands Regency, endemic species such as Paradisaea minor jobiensis are the main attraction for tourists. Managed by the community through local wisdom and the Dorey Jaya group, this area has the potential to be developed as birdwatching ecotourism. However, it has not been widely popular with tourists. This study aims to analyze changes in the vegetation of the bird's habitat for three periods (2014, 2018, and 2024) and provide recommendations for ecotourism management in Barawai. Vegetation structure and composition data were collected using the grid line method and analyzed using PAST software. The results showed an increase in the number of species at all vegetation levels, especially seedlings (21 species in 2014 to 72 in 2024), saplings (27 to 64), poles (26 to 76), and trees (41 to 96). The number of individuals also increased significantly, especially on saplings and poles. The diversity index also increased, especially at the tree level (2.78 to 4.07). This study indicates an increase in overall vegetation, with recommendations for optimizing ecotourism management based on biodiversity and local wisdom.